2020
DOI: 10.1186/s12957-020-1796-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ALDH2 rs671 and CYP2E1 rs2031920 with hepatocellular carcinoma susceptibility in East Asians: a meta-analysis

Abstract: Background: Aldehyde dehydrogenase 2 (ALDH2) and cytochrome p450 2E1 (CYP2E1) are important alcoholmetabolizing enzymes. The aim of this meta-analysis was to evaluate the association of ALDH2 rs671 and CYP2E1 rs2031920 polymorphisms with hepatocellular carcinoma (HCC) susceptibility in East Asians. Methods: A systematic search strategy was implemented in MEDLINE, PubMed, Scopus, Embase, and China Academic Journals databases. Nineteen case-control studies were selected for inclusion. Pooled odds ratios (ORs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…A meta-analysis conducted by Chen et al . 77 found that the ALDH2 rs671 polymorphism is not associated with HCC susceptibility in East Asians, and this is similar to the conclusion from Liu et al . 35 Interestingly, Huang et al .…”
Section: Related Liver Diseasessupporting
confidence: 89%
See 2 more Smart Citations
“…A meta-analysis conducted by Chen et al . 77 found that the ALDH2 rs671 polymorphism is not associated with HCC susceptibility in East Asians, and this is similar to the conclusion from Liu et al . 35 Interestingly, Huang et al .…”
Section: Related Liver Diseasessupporting
confidence: 89%
“…75 Recently, a study involving both mice and human patients showed that ALDH2 gene deficiency correlates well with a higher risk for advancement of alcohol related-fibrosis to HCC. 76 A meta-analysis conducted by Chen et al 77 found that the ALDH2 rs671 polymorphism is not associated with HCC susceptibility in East Asians, and this is similar to the conclusion from Liu et al 35 Interestingly, Huang et al 78 found that the ALDH2 polymorphisms had a certain impact on resolution of HCC in patients. The result showed that HCC patients with a defective allele of ALDH2 have a promising postoperative outcome, after Kaplan-Meier analysis and univariate followed by multivariate Cox proportional hazard analysis indicated that the GG genotype is an independent clinical predictor for shorter time-to-distant metastasis (adjusted p=0.019) and shorter overall survival (adjusted p=0.001).…”
Section: Hepatocellular Carcinomasupporting
confidence: 54%
See 1 more Smart Citation
“…A prognostic model involved apoptosis-related genes with impressive prognostic predictive power was also established in HCC [ 31 ]. Furthermore, numerous prognostic genes and prognostic signature for HCC have been reported by many studies [ 32 35 ] and further evaluated by some meta-analysis [ 36 , 37 ]. However, the relationship between pyroptosis and HCC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,14,33 For other cancers sites, existing genotypic evidence has been inconclusive. 15,16,19,22,[34][35][36][37][38] A previous meta-analysis of case-control studies found no clear associations of ALDH2-rs671 with cancers in the liver (1522 cases, 7 studies), colon-rectum (2356 cases, 10 studies), stomach (5558 cases, 8 studies) or lung (1105 cases, 2 studies). 15 In contrast, recent large case-control studies (>1000 cases each) in South Korea and Japan showed that ALDH2-rs671 AA and AG genotypes were associated with 22% to 30% lower risk of colorectal cancer, 16 but approximately 23% to 30% higher risk of stomach cancer, 19,38 compared to GG genotype.…”
Section: Discussionmentioning
confidence: 99%